THE LABOR ABSORBTION IN FOOD AND BEVERAGES OF SMALL BUSINESS ENTERPISES IN ACEH PROVINCE - Ishak Hasan; Yasrizal Yasrizal (AFEBI Economic and Finance Review, 2016)
The competition of labor market in Asean Economic Society will be determined by the labor’s productivity. Small businesses of foods and beverages is the highest sub sector which recruit the labor in Aceh. In 2010 there were 929.910 small businesses which were able to recruit 2.152.981 labor or around 31,99%. There are three variables impact the absorbtion of labor, the wages, labor productivity and capital. This research uses multiple regression technique to analyse data. The technique analysis used to find the impact of wages, productivity and capital to the absorbtion of labor in small businesses and enterprises. Based on research finding, the competitive advantage of Indonesian labor is at the sixth rank of ten countries in ASEAN. The research also found that productivity has significant impact to the absorbtion of labor while capital and wages have no significant impact to the absorbtion of labor in Aceh Province.JEL Classification: J01, J24, L66Keyword: AEC, Capital, Labor Competitiveness, Productivity, Wages